2020
DOI: 10.1083/jcb.201908232
|View full text |Cite
|
Sign up to set email alerts
|

Factors promoting nuclear envelope assembly independent of the canonical ESCRT pathway

Abstract: The nuclear envelope (NE) undergoes dynamic remodeling to maintain NE integrity, a process involving the inner nuclear membrane protein LEM2 recruiting CHMP7/Cmp7 and then ESCRT-III. However, prior work has hinted at CHMP7/ESCRT-independent mechanisms. To identify such mechanisms, we studied NE assembly in Schizosaccharomyces japonicus, a fission yeast that undergoes partial mitotic NE breakdown and reassembly. S. japonicus cells lacking Cmp7 have compromised NE sealing after mitosis but are viable. A genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 68 publications
2
36
0
Order By: Relevance
“…Importantly, LEM2 assembly at the reforming nuclear envelope occurred in the absence of CHMP7, suggesting that LEM2 is upstream and does not form part of the ESCRT-III polymer. However, consistent with recent reports from S. japonicus [16,17], LEM2's failure to be disassembled in the absence of CHMP7 suggests that CHMP7 acts to decluster and proper release of LEM2, allowing it to correctly populate the INM. Our biochemical data indicate that polymeric CHMP7 can capture LEM2, raising the possibility that this INM protein may instead be a 'cargo' that is actively sorted onto the INM through the activity of CHMP7 at sites of annular fusion.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Importantly, LEM2 assembly at the reforming nuclear envelope occurred in the absence of CHMP7, suggesting that LEM2 is upstream and does not form part of the ESCRT-III polymer. However, consistent with recent reports from S. japonicus [16,17], LEM2's failure to be disassembled in the absence of CHMP7 suggests that CHMP7 acts to decluster and proper release of LEM2, allowing it to correctly populate the INM. Our biochemical data indicate that polymeric CHMP7 can capture LEM2, raising the possibility that this INM protein may instead be a 'cargo' that is actively sorted onto the INM through the activity of CHMP7 at sites of annular fusion.…”
Section: Discussionsupporting
confidence: 86%
“…These data suggest that LEM2 must effectively gain chromatin tethers during mitotic exit to localise CHMP7 polymerisation to the reforming NE, and that persistent LEM2 in the peripheral ER can seed inappropriate CHMP7 polymerisation during mitotic exit. In S. japonicus, Cmp7 plays a role in disaggregating Lem2 clusters during interphase and mitotic exit [16,17]. In mammalian cells, we found that CHMP7 depletion led to persistent enrichment of LEM2 at the reforming NE ( Figure 1C, Figure 1D and Movie 4), suggesting that CHMP7 acts additionally to disassemble LEM2 and promote its mobility within the INM.…”
mentioning
confidence: 82%
“…Human and yeast LEMD2 directly interact with CHMP7 through their WH domains [98,99]. In the absence of CHMP7, yeast LEMD2 accumulates in patches that interfere with ESCRT-independent membrane sealing [101]. The dominant APS-associated mutation Ser479Phe might therefore either modify the predicted DNA-binding capacity of the LEMD2 WH domain (Fig.…”
Section: Recessive Mutations Causing Aps Disrupt the Lamin A/c-baf Inmentioning
confidence: 99%
“…Such an idea would be consistent with the emerging role of PA in several other membrane fusion events, e.g. COPI vesicle formation (Yang et al, 2008; Park et al, 2019) and exocytosis (Zeniou-Meyer et al, 2007; Miner et al, 2017) among many others (Corrotte et al, 2006; Nakanishi et al, 2006; Liu et al, 2007; Yang et al, 2008; Giridharan et al, 2013; Bates et al, 2014; Adachi et al, 2016; Starr et al, 2016), and could ultimately underlie genetic relationships defined between PA-metabolism and nup genes (Siniossoglou et al, 1998; Tange et al, 2002; Santos-Rosa et al, 2005; Costanzo et al, 2016; Lord and Wente, 2020) and those that link lipid metabolism more generally to nuclear envelope function (Gorjánácz and Mattaj, 2009; Domart et al, 2012; Bahmanyar et al, 2014; Grillet et al, 2016; Romanauska and Köhler, 2018; Ventimiglia et al, 2018; Kinugasa et al, 2019; Barbosa et al, 2019; Kume et al, 2019; Lee et al, 2020; Penfield et al, 2020). Definitively testing such a model requires more effective tools to precisely toggle PA levels with nanometer precision; recently developed light-inducible tools might provide a way forward here in the future (Tei and Baskin, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…4 D); this may have the added benefit of promoting the ultimate annular fusion event necessary for nuclear envelope sealing. Similarly, membrane remodeling by ESCRTs may itself increase local membrane tension (Booth et al, 2019) and trigger a local lipid synthesis response, which may contribute membrane to help seal nuclear ruptures (Kinugasa et al, 2019) and the nuclear envelope at the end of mitosis (Lee et al, 2020; Penfield et al, 2020).…”
Section: Resultsmentioning
confidence: 99%